Identifying the etiological profile of children presented with hepatomegaly admitted to a tertiary care hospital - Quan, Nguyen Khoi; Duc, Nguyen Huu Chau (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Objectives: To identify the pattern and etiology of diseases in children presented hepatomegaly at Pediatrics Department in Hue Central Hospital, Vietnam. Material and Methods: The Present study was conducted to evaluate the possible etiology and clinical features of children presented with hepatomegaly. A total of 107 children, from one month to fifteen years of age with hepatomegaly admitted in the Pediatric Department of Hue Central Hospital, Vietnam from May 2018 to April 2019 were included in this study. Results: The most common causes of hepatomegaly were inflammation/infection of the liver (miscellaneous cause included), hematological diseases and congestion heart failure with the percentage of 50.5%; 27,1% and 12,1%; respectively. Among the hepatitis group, viral agents account for nearly 50.0%, of which the most common one was Cytomegalovirus accounting for nearly 30.0%. Distribution of causes by age group revealed most cases in 1 year-old or younger children was caused by inflammation (53.8%), and in the older than 1 year-old children were hematological disorders (47.3%) which has statistical significance (P<0.05). Conclusions: Our research observed that the most common causes of the group of ≤ 1 year old were hepatitis, followed by cardiovascular disease and biliary obstruction due to congenital biliary atresia, and in the older than 1 year group, hematological disorders was the most common.